2009
DOI: 10.1016/j.athoracsur.2009.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Stroke in Infants Undergoing Open Heart Operations for Congenital Heart Disease

Abstract: . INVITED COMMENTARYI read with interest the article by Chen and colleagues [1]. A 10% incidence of perioperative stroke is a possible partial explanation for less than ideal neurodevelopmental outcomes in congenital heart disease (CHD) [2,3]. Additional explanations are genetic causes [4], fetal development with CHD, and injury that is not measured by imaging. If we are to improve neurologic outcomes, there are four areas in which practice improvement needs to become uniform or further explored: (1) prenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 20 publications
0
68
1
1
Order By: Relevance
“…70 Low brain maturity scores have been shown to be associated with a higher risk of acquired brain injury in newborns with CHD. 132 Chen et al 79 found that the incidence of stroke on brain MRI in infants who had undergone an operation with CPB for CHD was 10%; however, most strokes were clinically silent and would not have been detected in the short-term without the use of neuroimaging. Another study found that the incidence of periventricular leukomalacia in neonates with CHD increased from 16% before surgery to 48% after surgery.…”
Section: Significant Abnormalities On Neuroimaging or Microcephalymentioning
confidence: 99%
See 2 more Smart Citations
“…70 Low brain maturity scores have been shown to be associated with a higher risk of acquired brain injury in newborns with CHD. 132 Chen et al 79 found that the incidence of stroke on brain MRI in infants who had undergone an operation with CPB for CHD was 10%; however, most strokes were clinically silent and would not have been detected in the short-term without the use of neuroimaging. Another study found that the incidence of periventricular leukomalacia in neonates with CHD increased from 16% before surgery to 48% after surgery.…”
Section: Significant Abnormalities On Neuroimaging or Microcephalymentioning
confidence: 99%
“…However, early ischemic stroke 175 or white matter injury 176 may be missed on head CT, because perioperative strokes in this population may be clinically silent. 79 Therefore, further imaging with MRI should be obtained as soon as clinically feasible. 177 Although MRI has been used to measure and differentiate the neurological impact of various surgical strategies on the brain, 77,178,179 the indications for brain MRI for the asymptomatic child with CHD are poorly defined given the unclear prognostic value of abnormal findings and the lack of a consensus on the need for treatment of asymptomatic periventricular leukomalacia.…”
Section: Structural Brain Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that clinically silent ischemic strokes are quite common postoperatively in children as well as adult patients 8, 26, 27. Our study was limited to clinically evident ischemic strokes and clinically silent strokes were not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 30% incidence of stroke was noted in the Berlin Heart EXCOR pediatric ventricular assist device trial 46 ; it is as high as 10% in newborns undergoing open-heart surgery. 47 Improved prevention and management of stroke will require (1) better methods to diagnose and assess the severity of stroke (ischemic and hemorrhagic), (2) defining risk factors and causes of stroke, and (3) defining the pattern and determinants of long-term outcome. Barriers to progress are numerous, including (1) the poor reliability of clinical diagnosis in very young and critically ill children, (2) the need for MRI to ensure specific and timely diagnosis, (3) a lack of noninvasive bedside neuromonitoring methodologies, and (4) a limited availability of neurovascular expertise and lack of stroke care pathways in many institutions.…”
Section: Observational Studies -Stroke: Timely Assessment and Intervementioning
confidence: 99%